Factors impacting 1-year mortality after hip fractures in elderly patients: A retrospective clinical study - Gurger, M. (Wolters Kluwer Medknow Publications, 2019)
Background: This study aimed to evaluate risk factors that impact 1-year mortality in elderly patients with hip fractures after treatment with primary arthroplasty and proximal femoral nail. Patients and Methods: Overall, 109 patients aged >= 65 years with nonpathological hip fractures, treated between 2015 and 2016, were included in this study. Thirty-nine patients (35.8%) were treated with primary arthroplasty, and 70 patients (64.2%) were treated with proximal femoral nail. To determine whether the risk factors affected mortality, KaplanuMeier and log-rank analyses were conducted, and a Cox regression analysis was conducted to include the factors determined to have an impact on mortality. Results: Twelve patients (11%) died during hospitalization, and 24 patients (22%) died within 1 year after discharge from the hospital. The mortality risk was high for patients who underwent surgery 72 h after fracture, who could not independently perform their daily activities before the operation, had accompanying diseases, had an American Society of Anaesthesiologists score of 3 or 4, and had postoperative complications. There was no statistically significant difference between primary arthroplasty group and proximal femoral nail group with respect to mortality risk. Conclusion: Delayed surgery and postoperative complications may be the most important risk factors increasing 1-year mortality in elderly patients with hip fractures after treatment with primary arthroplasty and proximal femoral nail. These two risk factors can be prevented with proper precautions, and the rate of 1-year survival for these patients can be increased.
Keywords: Aged; hip fractures; mortality; risk factors